On modeling the martensite nucleation on ferromagnetic clusters - Yu. V. Dolgachev; V. N. Pustovoit; I. O. Filonenko; I. V. Ivankov (Advanced Engineering Research)
Introduction. The study of the austenite magnetic state in steels has provided the mechanism of the external magnetic field impact on steel under the hardening process. Previous studies have established a positive practical effect of heat treatment in a magnetic field. The work objectives were to create a computer model of the magnetic state of carbon steel austenite; to conduct computational experiments with a system of spins at various values of temperature and external magnetic field.Materials and Methods. The positions of the Ising model were used. The canonical ensemble of spins was modeled by the Monte Carlo method using the Metropolis algorithm.Results. The algorithm was implemented with the initial parameters selected through experimental data on the magnetic state of austenite. The inhomogeneity of this state without exposure to a magnetic field was studied. Data on the sizes of ferromagnetic clusters in austenite at various temperatures were obtained. It has been noted that the presence of an external magnetic field counteracts the temperature disordering of spins. Data on an increase in the size of ferromagnetic clusters under growing magnetic field strength were obtained.Discussion and Conclusions. A two-dimensional computer model of the spin state of austenite of carbon steel has been developed. The computational experiments with various parameters of the model have shown that there is a short-range order in the arrangement of spins above the Curie temperature. With a rise of the temperature of the system, the sizes of ordered regions decrease; but when an external magnetic field is applied, they increase.